EXPLORATION AND DETECTION OF SINKHOLE IN GOPENG, PERAK WITH EMPHASIS ON ELECTRICAL RESISTIVITY IMAGING - Binti Bidin, Nor Azlinda (Universiti Teknologi PETRONAS, 2015)
Sinkhole collapse is one of the main limitation on the development of karst areas, especially where bedrock is covered by unconsolidated material. Studies of sinkhole formation have shown that sinkholes area likely to develop when the limestone bedrock dissolve by flowing groundwater. Gopeng is believed to have a sinkholes beneath the Kinta Limestone which occurred during Paleozoic age. Being as the dominant lithology on study area, limestone bedrock can potentially produce sinkholes which may cause hazard towards people and surrounding areas. Therefore, further justification will be explained by using various assessment; geological and geophysical assessment. Electrical Resistivity Imaging (ERI) is well suited to map sinkholes because its ability to detect resistive features. Two- dimensional (2D) resistivity survey lines were conducted at S.M.K Idris Shah, Gopeng, where it believed to lies on a limestone bedrock with approximate depth of 20m. The between electrode spacing is set as 4m each. The length of line is 120m. The survey result suggest that ERI is an ideal geophysical tool to aid in the detection and monitoring of sinkholes. Result and analysis of this experiment will alert people on the potential hazard of sinkholes.